Green Deep Eutectic Solvents for Flavonoid Extraction - Hao Ruti (MATEC Web of Conferences)
Flavonoids have been broadly employed in diverse areas as they have the antioxidant, anticancer and hypoglycemic effects. Therefore, it is of great significance to extract high-purity and high-quality flavonoids. As the concept of green chemistry and sustainable development has been paid increasing attention and promotion. Deep eutectic solvents (DESs) have been proposed as a green solvent and used to replaced traditional extraction solvents for extracting flavonoids. Compared with conventional solvents, DESs have some benefits, including lower cost, sustainability, low toxicity and biodegradability. Besides, DESs can be combined with novel extraction technologies to enhance extraction efficiency. However, the extraction procedure of DESs is influenced by several factors such as their internal components and proportion, as well as external environmental factors. Therefore, the optimal extraction solvent and extraction conditions should be found in the process of extracting flavonoids. Moreover, the extensive industrial implementation and toxicity of eutectic solvent need to be further studied, and their cost-effectiveness, biological safety and cytotoxicity also need to be evaluated.